Polymer composite membrane as well as preparation method and application thereof

By using natural C@SiO2 phytosilite or TiO2@ phytosilite modified polyacrylonitrile films, the problem of difficulty in recycling adsorbents and photocatalytic materials in the wastewater treatment of rhodamine B was solved, and efficient rhodamine B removal effect was achieved, with good market prospects.

CN119505307APending Publication Date: 2025-02-25EAST CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411587544.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When treating Rhodamine B wastewater, it is difficult to recover adsorbents and photocatalytic materials, and the preparation cost is high, making it difficult to promote production applications.

Method used

Hydrophilic polyacrylonitrile is used as the main raw material, natural C@SiO2 physilite or TiO2@ physilite is used as functional modifiers, and the film is formed by blending phase conversion method to construct a porous polyacrylonitrile adsorption catalytic film, and the membrane structure is adjusted to improve adsorption and photocatalytic properties.

Benefits of technology

It has achieved efficient removal of rhodamine B, with a removal rate of more than 95%, rich reserves of modifiers, simple preparation process, and good market prospects and application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505307A_ABST
    Figure CN119505307A_ABST
Patent Text Reader

Abstract

The invention discloses a polymer composite membrane as well as a preparation method and application thereof. According to the composite membrane, natural phytic silica or a modifier thereof is used as a polymer composite membrane modifier, polyacrylonitrile is used as a main raw material of the composite membrane, and the membrane is formed by adopting a solution phase inversion method. Wherein the plant silica is a natural C-coated SiO2 material, the content of SiO2 is 65%-85%, the content of fixed carbon is 9%-20%, the plant silica has a porous structure, and the modified plant silica is TiO2 modified plant silica. The phase inversion speed of the polymer membrane casting solution can be changed, the membrane structure can be adjusted, and the membrane performance can be influenced by the introduction of the phyto-silica or the modifier thereof; the carbon-coated SiO2 in the modifier can improve the sunlight absorption of the film, the heat dissipation is small, and the rhodamine B photodegradation catalysis capability of TiO2 is enhanced; by changing the concentration of a polymer membrane casting solution, the use amount of the modifier and other process conditions, the membrane structure and the performance of adsorption and photocatalytic degradation of rhodamine B can be conveniently adjusted. And the composite membrane is simple in preparation process and good in rhodamine B dye wastewater treatment effect, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmentally friendly materials, and specifically relates to a polymer composite film and a preparation method and application thereof. Background Art

[0002] Rhodamine B is a water-soluble cationic dye, mainly used in industrial papermaking, paint, inkjet printing, dyeing of acrylic, hemp, silk and other fabrics, as well as straw and leather products, and in biological research. Rhodamine B can irritate the skin, respiratory tract and eyes when in contact with the human body, and is carcinogenic, so Rhodamine B in industrial wastewater must be separated and treated before it can be safely discharged.

[0003] Conventional treatment methods for Rhodamine B in wastewater include adsorption, photocatalytic degradation, biodegradation, membrane separation, oxidation, and electrodeposition. Among them, adsorption and photocatalysis are widely used. Subhasish M. designed and synthesized a visible light responsive composite catalyst gC 3 N 4 / NiFe 2 O 4 , the degradation rate of rhodamine B reached 98.6%. Some researchers used melamine, cyanuric chloride and ferric oxide as precursors and prepared magnetic covalent organic framework materials MCOFs by solvothermal method, and the adsorption capacity of rhodamine B was 12.8 mg / g. Zhang W. constructed BiFeO based on yeast 3 - Yeast composite material, the adsorption capacity of rhodamine B reached 59.4 mg / g. It should be pointed out that most granular adsorbents and photocatalytic materials are difficult to recycle, have high preparation costs, and are difficult to promote production and application. Summary of the invention

[0004] The object of the present invention is to provide a polymer composite membrane suitable for separation of rhodamine B to solve the problems raised in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] The purpose of the present invention is to provide a polymer composite membrane suitable for the separation of rhodamine B, using hydrophilic polyacrylonitrile as the main raw material and natural C@SiO 2 Phytolith or TiO 2 @ Phytosilicic acid is used as a functional modifier and deionized water is used as a coagulation bath. The porous polyacrylonitrile adsorption catalytic membrane is prepared by the mixed phase conversion method. The membrane structure is adjusted and the membrane performance is optimized by adjusting the dosage of the modifier, the concentration of the casting solution, and the residence time of the scraping film. 2 The structure improves the film's absorption of sunlight and enhances the TiO 2The ability to photodegrade and catalyze Rhodamine B. Compared with existing materials, under the condition of similar removal rate of Rhodamine B, the main body of the modifier is natural mineral, with unique structure, simple and efficient membrane preparation process, strong practical promotion, and good market prospects;

[0007] Based on the principle of membrane-based adsorption and photocatalysis, the present invention constructs a polymer composite membrane suitable for the separation of rhodamine B. The composite membrane uses natural phytolith or its modified product as a polymer membrane modifier, polyacrylonitrile as the main raw material of the composite membrane, and adopts a solution phase conversion method to form the membrane. Among them, phytolith is a natural C@SiO 2 Materials, SiO 2 The content is 65% to 85%, the fixed carbon content is 9% to 20%, and it has a porous structure. The modified phytolith is TiO 2 Modified products. The introduction of phytolith or its modified products can change the phase transformation rate of polymer casting solution, adjust the membrane structure, and affect the membrane performance; C@SiO 2 It can improve the film's absorption of sunlight, reduce heat dissipation, and enhance TiO 2 The ability to photodegrade and catalyze Rhodamine B; the membrane structure and the performance of adsorption and photocatalytic degradation of Rhodamine B can be easily adjusted by changing the concentration of the polymer casting solution, the amount of the modifier and other process conditions. The composite membrane has a maximum adsorption capacity of about 16 mg / g for 80 mg / L Rhodamine B solution, and after 100 minutes of illumination with one sun, the total removal rate of Rhodamine B is up to more than 95%. The reserve of the modifier is abundant, the preparation process of the composite membrane is simple, the effect of treating Rhodamine B dye wastewater is good, and it has good application prospects. No relevant reports have been found in the invention content.

[0008] A natural C@SiO suitable for the separation of rhodamine B 2 Polymer composite membrane, with polyacrylonitrile as the main raw material, naturally has C@SiO 2 Structure of phytolith or TiO 2 @Phytosilite is used as a modifier, N,N-dimethylacetamide is used as a solvent, and water is used as a coagulation bath, and the solution phase is transformed into a film. By adjusting the phytosilite or TiO 2 @The membrane structure and performance are adjusted by process conditions such as the amount of phytosil, solution concentration, and membrane residence time.

[0009] The present invention has at least the following beneficial effects:

[0010] 1. First use of natural C@SiO 2 Phytolith or TiO 2 @ Phytosilicic acid is used as a modifier for polymer membranes, especially polyacrylonitrile membranes, to construct composite membranes with high removal rates for rhodamine B. 2 It has the characteristics of high absorption rate of sunlight and low heat dissipation, which can effectively improve the 2The main body of the modifier is derived from natural non-metallic minerals, which is more cost-effective than most granular adsorbents and photocatalysts;

[0011] 2. Compared with granular adsorbents and photocatalysts, composite membrane materials have the advantage of easy recycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 For the present invention Figure 1 Phytolith and TiO 2 @SEM image of phytolith, where A is phytolith and B is TiO 2 @phytolith;

[0013] Figure 2 The present invention is a phytolith and TiO 2 @EDS image of phytolith, where A is phytolith and B is TiO 2 @phytolith;

[0014] Figure 3 The TiO 2 @XRD of phytolith;

[0015] Figure 4 These are surface SEM images of the PAN film of the present invention and the film of Example 2, where A is the PAN film and B is the film of Example 2. DETAILED DESCRIPTION

[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] Test Case

[0018] The present invention uses polyacrylonitrile as the main raw material and natural C@SiO 2 Structure of phytolith or TiO 2 @Phytosilite is used as a modifier, N,N-dimethylacetamide is used as a solvent, and water is used as a coagulation bath, and the solution phase is transformed into a film. By adjusting the phytosilite or TiO 2 @The membrane structure and performance are adjusted by process conditions such as the amount of phytosil, solution concentration, and membrane residence time.

[0019] The steps for testing the adsorption performance and photocatalytic performance of the composite film prepared by the present invention are as follows:

[0020] A 3 cm × 3 cm film was placed in a solution containing 15 mL of 80 mg / L rhodamine B. After being allowed to stand in the dark for 24 h, the concentration of the solution was measured using a spectrophotometer to calculate the adsorption capacity of the material.

[0021] The solution (containing the membrane) after 24 hours of static adsorption was placed under a 300W xenon lamp for illumination for a period of time, and the absorbance was measured. The concentration was calculated and compared with the initial concentration of the solution to calculate the total Rhodamine B removal rate.

[0022] Example 1

[0023] 0.5g of 0.5μm-5μm phytolith was ultrasonically dispersed in 45mL of N,N-dimethylacetamide solvent, and then 4g of polyvinyl pyrrolidone and 10g of polyacrylonitrile were added in sequence, stirred at 70°C for 6h, and a uniform casting solution was prepared for degassing. A certain amount of casting solution was poured on a glass plate, and the casting solution was quickly scraped flat with a 250μm scraper, and immediately placed in deionized water for phase conversion to form a membrane, and allowed to stand for 24h. After the solvent and water were completely replaced, product 1 was obtained.

[0024] Example 2

[0025] n-Butyl titanate, glacial acetic acid and anhydrous ethanol were added to a beaker in a volume ratio of 2:1:4, stirred thoroughly and mixed evenly to obtain solution A. In addition, ethanol and deionized water were mixed thoroughly in a volume ratio of 1:1 to obtain liquid B.

[0026] Next, liquid B was added to liquid A at a rate of 1 drop / second, with a volume ratio of liquid B to liquid A of 35:8, and stirred for 120 minutes to form a titanium dioxide sol. 3 g of phytolith sample with a particle size of 0.5 μm to 5 μm was placed in 40 mL of titanium dioxide sol and stirred, and after being fully mixed, it was transferred to a 100 mL hydrothermal reactor, heated at 200°C for reaction for 3 hours, and the modified phytolith was obtained after drying.

[0027] 0.4 g TiO 2 The modified phytolith was dispersed in 45 mL of N,N,-dimethylacetamide solvent, and then 0.5 g of polyvinyl pyrrolidone and 10 g of polyacrylonitrile were added, stirred at 70 ° C for 6 h, and prepared into a casting solution, and degassed. A certain amount of the casting solution was poured on a glass plate, and the casting solution was quickly scraped flat with a 250 μm scraper. After standing in the air for 30 seconds, it was placed in deionized water for phase conversion to form a membrane, and stood for 24 hours. After the solvent and water were completely replaced, product 2 was obtained.

[0028] Example 3

[0029] n-Butyl titanate, glacial acetic acid and anhydrous ethanol were added to a beaker in a volume ratio of 2:1:4, stirred thoroughly and mixed evenly to obtain solution A. In addition, ethanol and deionized water were mixed thoroughly in a volume ratio of 1:1 to obtain liquid B.

[0030] Next, liquid B was added to liquid A at a rate of 1 drop / second, with a volume ratio of liquid B to liquid A of 35:8, and stirred for 120 minutes to form a titanium dioxide sol. 3 g of phytolith sample with a particle size of 0.5 μm to 5 μm was placed in 50 mL of titanium dioxide sol and stirred, and after being fully mixed, it was transferred to a 100 mL hydrothermal reactor, heated at 200°C for reaction for 3 hours, and dried to obtain modified phytolith.

[0031] 0.5 g TiO 2 The modified phytolith was dispersed in 45 mL of N,N,-dimethylacetamide solvent, and then 4 g of polyvinyl pyrrolidone and 10 g of polyacrylonitrile were added, stirred at 70 ° C for 6 h, and prepared into a casting solution, and degassed. A certain amount of the casting solution was poured onto a glass plate, and the casting solution was quickly scraped flat with a 250 μm scraper. After standing in the air for 30 seconds, it was placed in deionized water for phase conversion to form a membrane, and stood for 24 hours. After the solvent and water were completely replaced, product 3 was obtained.

[0032] Example 4

[0033] n-Butyl titanate, glacial acetic acid and anhydrous ethanol were added to a beaker in a volume ratio of 2:1:4, stirred thoroughly and mixed evenly to obtain solution A. In addition, ethanol and deionized water were mixed thoroughly in a volume ratio of 1:1 to obtain liquid B.

[0034] Next, liquid B was added to liquid A at a rate of 1 drop / second, with a volume ratio of liquid B to liquid A of 35:8, and stirred for 120 minutes to form a titanium dioxide sol. 3 g of phytolith sample with a particle size of 0.5 μm to 5 μm was placed in 30 mL of titanium dioxide sol and stirred. After being fully mixed, it was transferred to a 100 mL hydrothermal reactor, heated at 200°C for reaction for 3 hours, and the modified phytolith was obtained after drying.

[0035] 2gTiO 2 The modified phytolith was dispersed in 45 mL of N,N,-dimethylacetamide solvent, and then 0.5 g of polyvinyl pyrrolidone and 7 g of polyacrylonitrile were added, stirred at 70 ° C for 6 h, and prepared into a casting solution, and degassed. A certain amount of the casting solution was poured on a glass plate, and the casting solution was quickly scraped flat with a 250 μm scraper. After standing in the air for 30 seconds, it was placed in deionized water for phase conversion to form a membrane. After standing for 24 hours, the solvent and water were completely replaced to obtain product 4.

[0036] Example 5

[0037] In a beaker, n-butyl titanate, glacial acetic acid and anhydrous ethanol were added in a volume ratio of 2:1:4, stirred thoroughly, and mixed evenly to obtain solution A. In addition, ethanol and deionized water were mixed thoroughly in a volume ratio of 1:1 to obtain liquid B.

[0038] Next, liquid B was added to liquid A at a rate of 1 drop / second, with a volume ratio of liquid B to liquid A of 35:8, and stirred for 120 minutes to form a titanium dioxide sol. 3 g of phytolith sample with a particle size of 0.5 μm to 5 μm was placed in 50 mL of titanium dioxide sol and stirred. After being fully mixed, it was transferred to a 100 mL hydrothermal reactor and heated at 200 °C for 3 hours. After drying, the modified phytolith was obtained. 0.1 g of TiO 2 The modified phytolith was dispersed in 45 mL of N,N,-dimethylacetamide solvent, and then 3 g of polyvinyl pyrrolidone and 12 g of polyacrylonitrile were added, stirred at 70 ° C for 6 h, and prepared into a casting solution, and degassed. A certain amount of the casting solution was poured onto a glass plate, and the casting solution was quickly scraped flat with a 250 μm scraper. After standing in the air for 10 s, it was placed in deionized water for phase conversion to form a membrane, and stood for 24 h. After the solvent and water were completely replaced, product 5 was obtained.

[0039] Table 1 shows the properties of the composite membranes obtained in the examples

[0040]

[0041]

[0042] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0043] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.

Claims

1. A method for preparing a polymer composite film, characterized in that: Firstly, phytolith or modified phytolith is ultrasonically uniformly dispersed in N,N-dimethylacetamide solvent, then polyacrylonitrile is added, the temperature is raised and stirred to prepare a polyacrylonitrile casting liquid in which the modifier is uniformly dispersed, and finally a phase transformation film-forming method is adopted to prepare a polymer composite membrane, wherein the modified phytolith component is TiO2-modified wollastonite.

2. The method for preparing a polymer composite membrane according to claim 1, characterized in that: The preparation process of the TiO2-modified phytolith is as follows: n-butyl titanate, glacial acetic acid and anhydrous ethanol are sequentially added into a beaker in a volume ratio of 2:1:4, and the mixture is stirred sufficiently to obtain a solution A; Separately, ethanol and deionized water were fully mixed in a volume ratio of 1:1 to obtain liquid B; Next, liquid B was added to liquid A at a rate of 1 drop / second, with a volume ratio of liquid B to liquid A of 35:8, and stirred for 120 minutes to form a titanium dioxide sol; 3 g of phytolith sample with a particle size of 0.5 μm to 5 μm was placed in 30 mL to 50 mL of titanium dioxide sol and stirred. After being fully mixed, it was transferred to a 100 mL hydrothermal reactor, heated at 200° C. for reaction for 3 h, and the modified phytolith was obtained after drying.

3. The method for preparing a polymer composite membrane according to claim 1, characterized in that: The membrane preparation process is as follows: First, 0.1 g to 2 g of phytolith or modified phytolith with a particle size of 0.5 μm to 5 μm is added to 45 mL of N,N,-dimethylacetamide solvent and uniformly dispersed by ultrasonication; Then, 0.5 g to 4 g of polyvinyl pyrrolidone (PVP) and 7 g to 12 g of polyacrylonitrile (PAN) were added in sequence, stirred at 70° C. for 6 h, and prepared into a casting solution, and degassed; Finally, a certain amount of solution was poured onto a glass plate, and the casting liquid was quickly scraped flat with a 250μm scraper. After standing in the air for 0s to 30s, it was placed in deionized water for phase transformation into a membrane and stood for 24h. After the solvent and water were completely replaced, a polymer composite membrane was obtained.

4. The method for preparing a polymer composite membrane according to claim 1, characterized in that: The preparation process of the TiO2-modified phytolith is as follows: n-butyl titanate, glacial acetic acid and anhydrous ethanol are added to a beaker in a volume ratio of 2:1:4, stirred and mixed to obtain solution A, and ethanol and deionized water are mixed in a volume ratio of 1:1 to obtain liquid B; Next, liquid B was added to liquid A at a rate of 1 drop / second, the volume ratio of liquid B to liquid A was 35:8, and stirred for 120 minutes to form a titanium dioxide sol. 3 g of phytolith sample with a particle size of 0.5 μm to 5 μm was placed in 30 mL of titanium dioxide sol and stirred. After being fully mixed, it was transferred to a 100 mL hydrothermal reactor, heated at 200°C for reaction for 3 hours, and the modified phytolith was obtained after drying.

5. The method for preparing a polymer composite membrane according to claim 1, characterized in that: The membrane preparation process is as follows: Disperse 2g TiO2-modified phytolith in 45mL N,N,-dimethylacetamide solvent, then add 0.5g polyvinyl pyrrolidone and 7g polyacrylonitrile, stir at 70℃ for 6h to prepare a casting solution, and degas; A certain amount of casting liquid was poured onto a glass plate, and the casting liquid was quickly scraped flat with a 250 μm scraper. After standing in the air for 30 seconds, it was placed in deionized water for phase transformation into a membrane, and stood for 24 hours. After the solvent and water were completely replaced, a polymer composite membrane was obtained.

6. A polymer composite membrane prepared by the method according to any one of claims 1 to 5, characterized in that: Hydrophilic polyacrylonitrile is used as the main membrane raw material, natural C@SiO2 phytosilicone or TiO2@phytosilicone is used as the functional modifier, and deionized water is used as the coagulation bath.

7. Application of a polymer composite membrane in the efficient separation of rhodamine B, characterized in that: Use the polymer composite membrane as claimed in claim 6.